2016
DOI: 10.17795/jjnpp-30034
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Satureja khuzestanica Essential Oil Against Clinical Isolates of E. coli

Abstract: Background: In folk medicine, Satureja khuzestanica infusion is prescribed to use before the meals to treat muscle pains, indigestion, cramps, nausea, diarrhea, and infectious diseases, especially bladder infections and inflammations. Objectives: This study aimed to evaluate the antibacterial activity of S. khuzestanica essential oil against clinical isolates of E. coli from urinary tract infections. Materials and Methods:The chemical composition of S. khuzestanica essential oil was determined by gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Kamdem et al showed that carvacrol had no specific effect on Listeria monocytogenes at 37 °C but was effective at 55 °C [ 46 ]. Mahbubi et al studied the antibacterial properties of S. khuzestaniea essential oil on clinical isolates of Escherichia coli [ 47 ]. Jourabi et al examined the antimicrobial effects of S. khuzestaniea and Z. multiflora with broth microdilution method on E. coli , S. aureus , C. albicans and Aspergillus niger [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kamdem et al showed that carvacrol had no specific effect on Listeria monocytogenes at 37 °C but was effective at 55 °C [ 46 ]. Mahbubi et al studied the antibacterial properties of S. khuzestaniea essential oil on clinical isolates of Escherichia coli [ 47 ]. Jourabi et al examined the antimicrobial effects of S. khuzestaniea and Z. multiflora with broth microdilution method on E. coli , S. aureus , C. albicans and Aspergillus niger [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the essential oil of S. khuzestanica contained almost 93% carvacrol as the major component. Also other investigators have reported over 90% carvacrol content in the S. khuzestanica essential oils which is collected from different areas of Iran (11,15,24,25). The antimicrobial activity of carvacrol, a phenolic monoterpene has been shown that be related to the presence of a free hydroxyl group and their hydrophobic nature essential for damaging cell membranes (26).…”
Section: Discussionmentioning
confidence: 93%
“…The antibacterial activity of S. khuzestanica essential oil has been shown against a number of bacteria including Grampositive food pathogens, some members of Enterobacteriaceae, as well as Pseudomonas aeruginosa (13,14). Other recent studies have been shown that carvacrol-rich S. khuzestanica EO has antimicrobial activity against clinical urinary isolates of E. coli, a number of Gram-positive cocci and yeast strains (15,16). Also the effect of S. khuzestanica EO has been shown on the expression of the bap gene which is involved in biofilm formation and bla gene in antibiotic resistant A. baumannii using polymerase chain reaction (17,18).…”
Section: Introductionmentioning
confidence: 99%
“… 2016 ). Mahboubi and Kazempour ( 2016 ) evaluated in vitro antibacterial activity of S. khuzestanica essential oil, carvacrol and gentamicin and their synergistic effect on E. coli. They found that antibacterial activity of carvacrol was higher than essential oil.…”
Section: Satureja Spp (Lamiaceae)mentioning
confidence: 99%